Choosing Joy as Methodology in Journalism Research. (April 2021) - Parks, Perry
Abstract: This article seeks to complicate notions that research methods in journalism and media communication should necessarily be preceded or driven by research questions, suggesting that researchers who prioritize methods that bring them joy might discover questions they wouldn't otherwise know to ask. The article first explores methodology as a lifestyle choice through the framework of non-representational theory. It then examines literature on postcoding, which suggests that the coding practices found in much qualitative social science are unnecessary holdovers of positivism. The essay shows how spontaneously freestyle, open-ended postcoding analysis enabled the author to discover and intra-act with data in newly rich and authentic ways. Finally, the article examines how this style of research fits with the normative commitments of the discipline of journalism studies.